Keefektifan SIMASKEREN Terhadap Penemuan Kembali Arsip di Dinas Perpustakaan dan Kearsipan Kota Blitar - Martika Sri Alvintasari; Brillian Rosy (Universitas Negeri Surabaya, 2020)
AbstractThis study aims to describe the application of an electronic archive and archival management system (SIMASKEREN) in the Blitar City Regional Library and Archive Service, and to determine the effectiveness of the electronic archive and archival management system (SIMASKEREN) on the rediscovery of archives in the Blitar City Regional Library and Archives Service. The type of research used is descriptive research using a qualitative approach. The subjects of the research were employees at the Blitar City Regional Library and Archives Service who had worked for more than three years. Data collection techniques using interviews, observation, and documentation, while data analysis techniques include data reduction, presentation, and drawing conclusions and verification. From the results of the accuracy calculation done by researchers at the Blitar City Library and Archives Service, the Accuracy Number (AK) results are 0.4% where AK is recommended ranging from 0.5% to 3%, from these results it can be concluded that the SIMASKEREN in the office has not been effective against the rediscovery of archives in the Blitar City Library and Archives Service.Keywords: Rediscovery of Archives Service; Simaskeren; Qualitative Approach